Development of Multimedia Content for Public Relations of the Faculty of Information Technology and Digital Innovation, North Bangkok University - ลือลาภ, นงนภัส; คุ้มรอด, อัญชิสา; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research is developmental research aimed at: 1) develop multimedia media for public relations of the Faculty of Information Technology and Digital Innovation, North Bangkok University 2) evaluate the effectiveness of the multimedia media 3) examine the level of awareness of the target audience after viewing the multimedia media and 4) study the satisfaction of the target audience toward the multimedia media. The sample group in this study consisted of 30 upper secondary school students or individuals interested in pursuing higher education. The participants were selected through purposive sampling for the convenience of data collection. The research instruments used in this study included 1) multimedia media for public relations of the Faculty of Information Technology and Digital Innovation, North Bangkok University 2) an effectiveness assessment form for the multimedia media and 3) a questionnaire measuring satisfaction and awareness levels after viewing the multimedia media.           The research findings revealed that the developed multimedia achieved the highest level of effectiveness based on expert evaluation, with a mean score of 4.58 and a standard deviation of 0.55. The results of the awareness and satisfaction assessments from the sample group were at a high level. The mean score for awareness was 4.19 with a standard deviation of 0.62, while the mean score for satisfaction was 4.57 with a standard deviation of 0.50. In conclusion, the multimedia was effective and contributed to enhancing awareness, making it suitable for use in public relations activities in accordance with the established objectives.